ANALISIS PENGARUH CURRENT RATIO, NET PROFIT MARGIN, DEBT TO EQUITY RATIO, EPS, ARUS KAS BEBAS, DAN DIVIDEN TAHUN SEBELUMNYA TERHADAP DIVIDEN KAS - Ega Zuwita; Deliza Henny (Jurnal Akuntansi Trisakti, 2017)
Cash dividend is one form of return expected by shareholders. But on the other side, cash dividend is an expense for the company. This conflict of interest is a factor affecting the company in determine the amount of cash dividends. So, the researcher conducting research which aims to test and analyze the influence of Current Ratio, Net Profit Margin, Debt to Equity Ratio, EPS, Free Cash Flow, and Previous Year Dividend to Cash Dividend paid by company. The sample used in this reasearch is manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2014 to 2016. After sampling the results showed there are 17 companies that can be sampled with a period of three years. So the total sample in this research are 51 samples. The result of this research shows that (1) Current Ratio has positive effect to Cash Dividend, (2) Net Profit Margin has no effect to Cash Dividend, (3) Debt to Equity Ratio has no effect to Cash Dividend, (4) EPS has positive effect to Cash Dividend , (5) Free Cash Flow has no effect to Cash Dividend, (6) Previous Year Dividend has no effect to Cash Dividend.